Upper extremities Special Strength Exercises In some Angles And Performing Basket Skill on The Parallel Bar For Advance Iraqi Gymnastic League - Abbas, Saadullah; Fouad, Fareed (Journal of Physical Education, 2018)
Upper extremities Special Strength Exercises In some Angles And Performing Basket Skill on The Parallel Bar For Advance Iraqi Gymnastic League The research aimed at identifying the effect of upper extremities special strength exercises with certain angles on the performance of basket skill on the parallel bar in advance Iraqi gymnastic league. The researcher hypothesized significant statistical differences between pretests and posttests in some angels and performing Basket on the parallel bars. The researcher used the experimental method. The subjects were (3) gymnasts. The data was collected and treated using proper statistical operation to conclude that using upper extremities special strength exercises positively affected and developed the performance of basket on the parallel bars. Finally the researcher recommended using these exercises in all gymnastics centers for developing special strength and coaches should pay more attention to physical traits due to their great importance in developing all skills. Keywords: special strength, angels, basket, gymnastics, parallel bars.